Study of seismic orientation of structure with bi-directional response analysis in the vicinity of branched fault earthquake rupture. (March 2022) - Dwivedi, Adarsh; Karthik Reddy, K.S.K.; Somala, Surendra Nadh
Abstract: Ground motions originating from earthquakes on complex fault systems have a wide range of spatial variability whose understanding is limited as a result of scarcity in near-field ground motions. The objective of this study is to employ computational seismology by using state of the art tool (SPECFEM3D) in simulating and understanding dynamic earthquake ruptures in a branch fault system. Employing physics-based dynamic rupture simulations not only aids to model complicated fault systems but also allows to gather ground motion data at the desired coordinates which can then be extended to evaluate the response of structures near the fault zone for various earthquake scenarios. In this study, synthetic ground motions are generated for two different cases of rupture propagation by modeling dynamic earthquakes for the left-lateral and right-lateral branched faults systems. In both cases, nucleation initiates in the main fault but differs in the continuous rupture that propagates along (i) the main fault (case-1), and (ii) the branch fault (case-2). Simulated time histories are extracted at certain stations for the near-field as well as far-field and a vectorization based on the orientation of the building is applied. Further, bi-directional responses and Maximum-Radial Spectral Acceleration (Max-RSA) of the structure are produced to study the importance of building orientation with respect to fault line for both rupture scenarios. It is observed that the influence of orientation is minimal for near-field stations (Set-A), perceptible for far-field stations (Set-B) and quite predominant for far-field stations along the strike of the branch fault (Set-C).